PENINGKATAN MUTU MADRASAH UNGGULAN PADA MTsN BARABAI KALIMANTAN SELATAN - Erlina Farida (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2014)
Madrasah as a sub system of national education system has contributed to the cultural development of the nation. There has been misleading impression that madrasah is a marginal school. The Public Junior Secondary Madrasah (MTsN) of Barabai, South Kalimantan, as a model madrasah has proven to be the center of excellence. This paper provides a study on how MTsN Barabai improve their quality and develop innovative education forquality improvement. This study is purposed to determine how the quality policy and quality of innovation development are implemented. The results of this study demonstrate that the sincerity, hard work, and creativity of the managers in organizing student inputs to implementation process are successfully accomplished to achieve the objectives of student outputs as formulated in the madrasah policy.